KOMPOSISI DAN KEANEKARAGAMAN JENIS TERIPANG (HOLOTHUROIDEA) DI PERAIRAN PANTAI PASIR PUTIH PANGANDARAN JAWA BARAT - Winanto, Tjahjo; Any Kurniawati; Purwo Raharjo; Kasprijo; Nabela Fikriyya (Program Studi Teknologi Hasil Perikanan|Fakultas Pertanian|Universitas PGRI Banyuwangi, 2024)
Sea cucumbers are special marine resources that have high protein content and high economic value. Some of them are commercially important culture species in Asian countries. It is interesting to study, because the composition and diversity of sea cucumbers are influenced by the environment in which they live. The purpose of this study was to determine the composition and diversity of sea cucumbers (Holothuroidea) and water quality (salinity, temperature, dissolved oxygen and pH) suitable for the life of sea cucumbers (Holothuroidea) in the waters of Pasir Putih Beach Pangandaran, West Java. Sampling was conducted using line transect and quadrant transect methods, sea cucumber samples were collected by hand picking and then in-situ identified. The results showed that the highest species composition was Holothuria atra (29.62%), Stichopus sp. (25.93%), Holothuria scabra (18.52%), Synapta maculata (14.81%) and the lowest Holothuria marmorata. Sea cucumber diversity was categorised as low (H‘: 1.27-1.36) and the highest species diversity was Holothuria atra (H’: 1.06). The water quality at Pasir Putih Beach Pangandaran is quite good for sea cucumber (Holothuridea) life, with water parameters such as temperature ranging from 30-30.3 °C, salinity 31-31.5 ppt, pH 7.5-8, and dissolved oxygen (DO) 5.5 mg/l.